Recovery pattern of cyclone-affected coconut palms in littoral sandy soils of Orissa-Part I - G. C. Acharya; D. P. Ray; D. K. Dash (International Coconut Community, 2006)
The experiment to study the recovery pattern of cyclone affected coconut palms cv. Sakhigopal Local was carried out in an ongoing fertilizer trial with three levels each of N (500, 1000 and 1500 g N/palm/year), P (250, 500 and 750 g P2O5/palm/year) and K (750, 1250 and 1750 g of K2O/palm/year) at Coconut Research Station, Orissa University of Agriculture and Technology, Bhubaneswar, India. The rate of leaf production and number of functional leaves on the crown increased appreciably with nitrogen fertilization at 1000 g per palm per year as compared to 500 g per palm during early years of damage in all the three categories. The different levels of phosphorus fertilization did not influence the recovery of growth characters favourably.